Goodby Columbus and all that: history and textual criticism - Teofilo F. Ruiz (NWIG, 1993)
[First paragraph]
Columbus. FELIPE FERNANDEZ-ARMESTO. Oxford: Oxford University Press, 1991. xxvii + 218 pp. (Cloth US$ 16.95, Paper US$ 6.99)
The Worlds of Christopher Columbus. WILLIAM D. PHILLIPS, JR. & CARLA RAHN PHILLIPS. Cambridge: Cambridge University Press, 1992. xii + 322 pp. (Cloth US$ 27.95)
In Search of Columbus: The Sources for the First Voyage. DAVID HENIGE. Tucson: University of Arizona Press, 1991. xiii + 359 pp. (Cloth US$ 29.95)
Columbus and the Golden World of the Island Arawaks: The Story of the First Americans and Their Caribbean Environment. D.J.R. WALKER. Kingston, Jamaica: Ian Randle, 1992. 320 pp. (Cloth US$ 12.95)

By the time this review appears in print, the Quincentenary celebrations and/or deprecations of the event will be slowly fading into most welcomed oblivion. There will be, of course, the unavoidable local commemorations of specific events: the discovery of such and such island, the anniversary of some European misdeed, the struggle for the valley of Mexico; but the collective remembrance of the Encounter/Discovery will have been allowed to run its course. In truth, after a veritable flood of publications, seminars, operas, protests, and ghastly movies, one is not too sorry to see the whole affair put safely away for another century. If there is any consolation to this continuous process of recovered memories and history, it is that a good number of sensible and scholarly works have been published - including some of those reviewed here - which demolish the idealization and glorification of the Atlantic enterprise and set the history of the Encounter/Discovery within a proper historical context.